Synthesis of isomeric coumarin-fluorene hybrids by photocyclization and the photophysical features. Issue 13 (28th March 2018) - Yamaji, Minoru; Okamoto, Hideki; Goto, Kenta; Kato, Shin-ichiro; Tani, Fumito; Nakamura, Yosuke
Graphical abstract: Highlights: Compounds2a and2b were prepared by photochemical cyclization of olefin1 . Isomers2a and2b were separated and characterized by X-ray crystallography. The molecular structure of2a was nonplanar whilst that of2b was planar. Difference and similarity in the photophysical features in solution were discussed. Abstract: We prepared isomeric compounds2a and2b having fused skeletons of coumarin and fluorene by photochemical cyclization of olefin1 . They were successfully separated by chromatography, and characterized by NMR spectroscopic and X-ray crystallographic analyses. The molecular structure of2a was nonplanar due to the repulsion between the carbonyl group of the coumarin moiety and the methylene group at 9-position on the fluorene skeleton whilst that of2b was planar. They showed different absorption and fluorescence features in solution whereas their spectral profiles of triplet–triplet absorption and phosphorescence were similar to each other.